Policy Challenges and Opportunities: Migrant Female Entrepreneurs in Northern Europe - Falcão, Roberto P. Q.; Barboza C. Cunha, Victoria (Journal of Comparative International Management)

(untitled) (Management Futures, 2024)
The article examines the profound influence of public policies on female migrant entrepreneurship, emphasizing their impact at both local and global levels. Highlighting diverse obstacles faced by female entrepreneurs, including financial constraints, limited knowledge, gender bias, and sociocultural factors, it underscores the pivotal role of governmental support. Specifically, in Northern Europe, gender equality, integration, and entrepreneurship policies are identified as crucial facilitators. Thus, migrant women, facing compounded challenges of gender, ethnicity, and immigration status, encounter barriers to accessing local opportunities. Motivations for entrepreneurship span economic survival, flexibility, and escape from domestic challenges. However, low-tech migrant enterprises often remain overlooked. Women’s business groups and governmental initiatives emerge as vital sources of support, emphasizing the need for tailored policies benefiting female entrepreneurs, especially migrants. The integration of such policies within broader entrepreneurial ecosystems ensures alignment and mutual reinforcement, thus policymakers are urged to recognize and address the distinct needs of female migrant entrepreneurs.